Patterns of Inclusion: How Gender Matters for Automation, Artificial Intelligence and the Future of Work - Elisabeth Kelan (Routledge, 2025)
It is widely presumed that digitalisation, automation and artificial intelligence (AI) shape the future of work; yet, gender is rarely considered in those debates. This ground-breaking book, written by a leading thinker on gender, inclusion and organisations, is based on in-depth research to show which patterns of gender and digitalisation emerge. By weaving these different patterns together, is it possible to understand the dynamic and complex ways gender and digitalisation intertwine in the work context? The book highlights how futures of work are imagined between automation and augmentation: it shows which tasks are expected to be done by machines, and where humans are expected to have a competitive advantage. The book showcases how algorithmic bias is constructed as ultimately fixable, and analyses in/visibilities in AI production processes. Above all, the book shows how patterns relating to gender and inclusion are shaped and could be re-shaped. This innovative book provides a stimulating and provocative read for those who are interested in how automation and AI shape the future of work in regard to gender and what this means for inclusion.
Keywords: 330; Diversity; Technology management; Artificial Intelligence; Gender; Gender management; Binary; Workplace diversity; Organizational development; Organisational culture